Multicenter, retrospective, comparative study of laparoscopic and open Kasai portoenterostomy in children with biliary atresia from Japanese high‐volume centers. (12th January 2019) - Murase, Naruhiko; Hinoki, Akinari; Shirota, Chiyoe; Tomita, Hirofumi; Shimojima, Naoki; Sasaki, Hideyuki; Nio, Masaki; Tahara, Kazunori; Kanamori, Yutaka; Shinkai, Masato; Yamamoto, Hirotoshi; Sugawara, Yasuhiko; et al.
Abstract: Background: Multicenter study was undertaken to analyze the results of laparoscopic and open Kasai portoenterostomy. Methods: Subjects were infants with type III biliary atresia who underwent open operation ( n = 106) or laparoscopic operation ( n = 21) between January 2012 and December 2015. Clinical data were compared between open and laparoscopic operations (2016‐0534). Propensity score matching was performed to reduce the effect of treatment selection bias. Multivariate analyses were used to estimate the effect of the surgical approach on the jaundice clearance rate and the native liver survival rate. Results: The postoperative jaundice clearance rate and the 1‐year native liver survival rate were not significantly different between open and laparoscopic operations. Rates of cholangitis and major complications of laparoscopic operation were comparable to those of open operation. Blood loss, time to resume oral intake, time to drain removal, and duration of analgesic usage of laparoscopic operation were significantly superior to those of open operation. Similar results were observed when analysis was adjusted based on propensity score. Multivariate analyses demonstrated that only age at operation was a poor prognostic factor. Conclusion: Laparoscopic Kasai portoenterostomy was associated with several favorable perioperative outcomes compared with open Kasai portoenterostomy. The difference of surgical approach was not a significant independent predictor. Abstract : Highlight In this multicenter study, Murase and colleagues analyzed patients with biliary atresia who underwent either open or laparoscopic Kasai portoenterostomy. The laparoscopic procedure was associated with several favorable perioperative outcomes. The difference in surgical approach was not a significant independent predictor, and only age at surgery was a poor prognostic factor.